Upaya Guru Bimbingan Konseling dalam Menangani Perilaku Prokrastinasi Akademik Siswa di MTs Al - Ittihadiyah Laut Dendang - Akhir Pardamean Harahap; Diki Ananta Sembiring; Shofiyah Nabila (Journal on Education, 2023)
This tendency to procrastinate in psychology is known as procrastination. The main task of educators is to help mature students, mature psychologically, socially and morally. A guidance and counseling teacher who is engaged specifically in understanding student problems at school needs to try to deal with procrastination problems experienced by students. This article aims to find out the efforts of counseling guidance teachers in dealing with procrastination behavior in academic matters of students at MTsS Al-Ittihadiyah Dendang Sea. This research uses a descriptive qualitative method with a case study approach. The data collection technique used is the data collected from various sources and the results of this study only apply to the cases investigated. guidance and counseling teacher efforts in overcoming academic procrastination behavior at MTsS Al-Ittihadiyah by identifying procrastination behavior and when receiving reports from subject teachers then guidance and counseling services are given to these students.